Islamic Boarding School Management in Forming A Culture of Student Discipline (Case Study at the Ulul Albab Manisrenggo Islamic Boarding School Foundation, Kediri City District) - Syahnas Nabila Al Auliya (International Journal of Religion and Social Community, 2023)
Education is a process of transformation within individuals, groups and the environment that is comprehensive and sustainable. Therefore, education is an important element that cannot be separated from human life. Education aims to form human personalities who have noble character, are independent, and comply with the norms found in society. Islamic boarding school is an Islamic educational institution which not only focuses on teaching Islamic values and forming morals, but also focuses on forming the character of students who are independent and disciplined. Education at Islamic boarding schools is famous for its dormitory model education which is structured, disciplined, and strong with Islamic values. Discipline is an attitude that must be cultivated and applied in everyday life. A disciplined attitude can shape the character of students so that they obey the rules contained in the Islamic boarding school. Implementing a disciplined attitude through Islamic boarding school culture which is carried out repeatedly will create a conducive and orderly situation in carrying out activities within the Islamic boarding school. However, in its implementation there are still several obstacles , even though if it can be implemented optimally all activities in the Islamic boarding school can be arranged and implemented in a timely manner. This research uses a descriptive qualitative research method, which is a method that reveals events or facts, circumstances and phenomena that occurred during the research and presents the facts in the field. The results of this research are that the disciplinary attitude possessed by the students at the Ulul Albab Islamic Boarding School Foundation is formed because of the application of disciplinary attitudes in every activity within the Islamic boarding school.